The scorch trials eaudiobook - Dashner, James (Maze Runner, 2010)
Book two in the blockbuster Maze Runner series that spawned a movie franchise and ushered in a worldwide phenomenon! And don’t miss The Fever Code, the highly-anticipated series conclusion that finally reveals the story of how the maze was built!      Thomas was sure that escape from the Maze would mean freedom for him and the Gladers. But WICKED isn’t done yet. Phase Two has just begun. The Scorch.    The Gladers have two weeks to cross through the Scorch—the most burned-out section of the world. And WICKED has made sure to adjust the variables and stack the odds against them.    There are others now. Their survival depends on the Gladers’ destruction—and they’re determined to survive.    Friendships will be tested. Loyalties will be broken. All bets are off. The Maze Runner and Maze Runner: The Scorch Trials , and Maze Runner: The Death Cure are all now major motion pictures featuring the star of MTV's  Teen Wolf , Dylan O’Brien; Kaya Scodelario; Aml Ameen; Will Poulter; and Thomas Brodie-Sangster.   Also look for James Dashner’s edge-of-your-seat MORTALITY DOCTRINE series! Praise for the Maze Runner series: A #1  New York Times  Bestselling Series A  USA Today  Bestseller A  Kirkus Reviews  Best Teen Book of the Year An ALA-YASLA Best Fiction for Young Adults Book An ALA-YALSA Quick Pick   “[A] mysterious survival saga that passionate fans describe as  a fusion of  Lord of the Flies ,  The Hunger Games , and  Lost . ” — EW   “Wonderful action writing —fast-paced …but smart and well observed.” — Newsday   “[A]  nail-biting  must-read.” — Seventeen   “Breathless,  cinematic action. ” — Publishers Weekly   “ Heart pounding  to the very last moment.” — Kirkus Reviews   “ Exclamation-worthy. ” — Romantic Times   “James Dashner’s illuminating prequel [ The Kill Order ] will thrill fans of this Maze Runner [series] and prove just as  exciting for readers  new to the series.” — Shelf Awareness , Starred “ Take a deep breath before you start  any James Dashner book.” — Deseret News